Analysis of User Perceptions of Transport Service Performance in Makassar City - Halim, Didin; H, Herman (Jurnal Ilmiah Ilmu Administrasi Publik, 2020)
Changes in the arrangement of transportation system services in Makassar City must be made immediately in realizing public transportation systems that meet the expectations and needs of the community. There are problems with the performance of Pete-Pete's public transport services in terms of reliability, comfort, security, generosity, and timeliness of pete-pete public transport in Makassar City. The purpose of this study is to analyze the description of users' perceptions of public transport and examine the effect of reliability, comfort, security, generosity and timeliness on the performance of public transport in Makassar. This research uses a quantitative approach with data collection techniques through observation, questionnaires and in-depth interviews and documentation studies. The research sample of 150 people as respondents. This study uses SEM analysis with the SmartPLS package program ver. 2.0 ME, to estimate the model, study and test hypotheses. The results of this study indicate that (i) There is a positive influence on the reliability factor on the performance of Pete-Pete transportation in Makassar City, with a contribution of 44.30% (ii) There is a positive influence of comfort factor on the performance of Pete-Pete transportation in Makassar City, with the contribution of 26.35%, (iii) There is no positive effect on the performance of the Pete-Pete transportation performance in Makassar City, with a contribution of only 0.78%. (iv) There is a positive influence of the factor of mercy on the performance of Pete-Pete transportation in Makassar City, with a contribution of 54.23% and (v) There is a positive influence of the timeliness factor on the performance of Pete-Pete transportation in Makassar City, with a contribution of 60.50%.